Analysis of patients' narratives posted on social media websites on benfluorex's (Mediator®) withdrawal in France. (21st October 2013) - Abou Taam, M.; Rossard, C.; Cantaloube, L.; Bouscaren, N.; Roche, G.; Pochard, L.; Montastruc, F.; Herxheimer, A.; Montastruc, J. L.; Bagheri, H.
Summary What is known and objective Websites and discussion lists on health issues are among the most popular resources on the Web. Use experience reported on social media websites may provide useful information on drugs and their adverse reactions (ADRs). Clear communication on the benefit/harm balance of drugs is important to inform proper use of drugs. Some data have shown that communication (advisories or warnings) is difficult. This study aimed to explore the Internet as a source of data on patients' perception of risk associated with benfluorex and the impact of wider media coverage. Methods Three French websites were selected: Doctissimo, Atoute.org considered the best‐known and visited website in France for health questions and Vivelesrondes (Long live the Tubbies) for overweight people. Three periods were chosen: (1) before November 2009 (i.e. before benfluorex withdrawal), (2) between November 2009 and November 2010 (when the risk of valvulopathy with benfluorex appeared in social media) and (3) after November 2010. Results and discussion Two hundred twenty initial postings were analysed. These lead to 660 secondary postings which were analysed separately. In period 1, 114 initial postings were analysed, mostly concerning efficacy of the drug (72%). In period 2, 42 initial postings were analysed involving mainly ADRs or warnings (73%). In period 3, 64 initial postings were analysed; most frequent expressing anger directed at the healthcare system (58%) and anxiety about cardiovascular ADRs (30%). Online consumer postings showed that there were drastic changes in consumers' perceptions following media coverage. What is new and conclusion This study suggests that analysis of website data can inform on drug ADRs. Social media are important for communicating information on drug ADRs and for assessing consumer behaviour and their risk perception.